Pengaruh Core Strength Training Terhadap Keseimbangan Dinamis Pada Pemain Sepak Bola Usia 10-13 Tahun Di Ssb Madya Pemda Surakarta - Rahmawati, R.Rr. Novia; , Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2017)
Balance is a combination of muscle strength, flexibility, speed, agility, neuromuscular coordination and reaction speed. Core strenght targeted for abdominal muscle that connect hip, spine and shoulder, helping maintain good posture.Modifikasi bass test is a measuring instrument for dynamic balance. This type of research is quasi experimental with pre and post test with control group, the treatment group given sample core strength training for 4 weeks with a frequency of twice a week. While the sample in the control group did sustainable exercise in SSB. While the results of the analysis of the results obtained using wilcoxon test and Mann Whitney test. After statistical test using Wilcoxon test results of the treatment group p = 0.001 means that there is the influence of core strength training to balance dynamically on SSB Madya Pemda Surakarta and control group p = 0.180 result means no influence. After the Mann Whitney test p value = 0.000 means that there are different influences. there is influence of core strength training towards the dynamic balances of football players age 10-13 on the SSB Madya Pemda Surakarta. Keywords: Core Strength Training, Dynamic Balance, Football Players.